Developing a national e-health strategy for DR Congo: a preliminary analysis of business needs, existing information systems and solutions - Verbeke, Frank; Shamashanga, Pierrot; Amisi, Clément; Karara, Gustave (Journal of Health Informatics in Africa, 2015)
Background and purpose: In order to reclaim its leadership and to better align existing and future ICT implementations in the health domain with the strategic options defined by the National Plan for Health Development, the Ministry of Health (MoH) of the DRC initiated early 2014 the development of a national e-health enterprise architecture. During the preliminary phase of the architecture development cycle, an initial analysis of human resources, business processes, hardware, software, communication and networking infrastructure related to health information management, had to be established. Methods: A first part of the study consisted of a detailed analysis of regulatory documents and strategic plans related to the Congolese health system and health informatics development. In a second part, field visits and semi-structured interviews were organized with a representative sample of relevant health structures throughout the country Results: The study demonstrates the large number of business needs that must be addressed by e-health initiatives. It also documents the donor driven unequal distribution of hardware equipment over health administration components and health facilities. Internet connectivity remains problematic and few health oriented business applications found their way to the Congolese health system. Paper based instruments remain predominant in DRC’s health administration. The study also identified a series of problems introduced by the uncoordinated development of health ICT in DRC such as the lack of standardization, data security risks, poor data quality, inadequate ICT infrastructures, an unregulated e-health sector and insufficient human capacity. Conclusions: The results confirm the precarious situation of the Congolese health information system but they also expose a number of bright spots that provide hope for the future: a political will to reclaim MoH leadership in the health information management domain, the readiness to develop e-health education and training programs and the opportunity to capitalize the experiences from early successes with DHIS2 and a number of hospital information management systems.